Student’s Perception of English Language Learning Through the Wajar Dikdas Programme (Compulsory Education) at Sidogiri Banat 1 Islamic Boarding School - Nisa’, Mar’atun; Sholichah, Norma Ita (Sekolah Tinggi Agama Islam Al-Furqan, Makassar - Indonesia, 2026)
This study aims to explore students’ perceptions of English language learning through the Wajar Dikdas (Compulsory Education) programme at Sidogiri Banat 1 Islamic Boarding School, focusing on its usefulness and English teachers’ characteristics. A qualitative descriptive method was employed using questionnaires and interviews as data collection instruments. The participants consisted of 72 students involved in English learning activities within the programme. Questionnaire data were analyzed descriptively using percentages, while interview data were analyzed through thematic analysis. The findings indicate that students generally hold positive perceptions of English learning through the Wajar Dikdas programme (compulsory education), particularly in improving understanding, motivation, and classroom interaction. English teachers were perceived as friendly, motivating, and supportive. However, some students reported neutral perceptions regarding their confidence in speaking English. These findings suggest that while the programme effectively supports English learning in pesantren contexts, improvements in communicative teaching strategies are still needed.